PENGARUH EKSTRAK KULIT DELIMA (Punica granatum) DAN RUMPUT TEKI (Cyperus rotundus) TERHADAP MORTALITAS LARVA NYAMUK Aedes aegypti - Binawati, Diah Karunia; Amilah, Susie (WAHANA, 2014)
Dengue Haemorrhagic Fever (DHF) is nowadays one of the most common public health problems in Indonesia, which lately the number of patients and the range of dissemination tend to be increasing. The most simple and effective way to attempt termination of the life cycle of the mosquito Aedes aegypti is to kill mosquito larvae. Frankly, the act of using arviciding or chemical pesticides often cause these following problems such as environmental pollution, the emergence of resistance and disruption of the ecological balance. The use of plants as a natural pesticide that is environmental -friendly is one of the alternatives that could be done by the society. One of the ways is by using pomegranate peel extract (Punica granatum) and nut-grass extract (Cyperus rotundus). The skin of pomegranate contains saponins, flavonoids and polyphenols, flavonoids and polyphenols. While the nut-grass (Cyperus rotundus) contain alkaloids, flavonoids, cineol, pinene, siperon, rotunal, siperenon, and siperol. This study aims to determine whether there is the effect of giving pomegranate peel extract (Punica granatum) and extract of the nut-grass (Cyperus rotundus) against larvae of Aedes Agypti mortality during a 24-hour treatment. The research design used was a complete randomized design, with pomegranate peel extract treatment (0%, 5%, 10%, 15% and 20%), and extract the nut-grass (0%, 5%, 15% and 20%), each treatment was given 3 repetitions, and observed mortality of larvae of Aedes Agypti after treated for 24 hours. The results showed that 1. There is an effect of pomegranate peel extract against Aedes aegypti larvae mortality for 24 hours, and at a level of 20% has the highest mortality rate (12.5 ± 2.43) 2. There is an effect of nut-grass extract extract against Aedes aegypti larvae mortality for 24 hours, and at a level of 20% has the highest mortality rate (6 ± 1.14) 3. The extract of pomegranate skin has the ability to kill the larvae of Aedes aegypti greater than the extract of nut-grass